2010
DOI: 10.1186/1752-4458-4-31
|View full text |Cite
|
Sign up to set email alerts
|

Schizophrenia and quality of life: how important are symptoms and functioning?

Abstract: Objectivethe relationship between Quality of life (QoL) and global functioning and symptoms in outpatients with SchizophreniaMethodThe study was carried out on the outpatients with schizophrenia attending a Community Mental Health Centre in 2008. Each patient completed the WHO QoL Instrument - Brief and was administered the Brief Psychiatric Rating Scale-24 to assess psychiatric symptoms and the VADO Personal and social Functioning Scale to assess the level of functioning.Resultssubjects showed an intermediate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

15
79
1
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 84 publications
(97 citation statements)
references
References 30 publications
15
79
1
2
Order By: Relevance
“…This clearly showed improvement in the medication adherence and QOL of the BPAD patients in test group which meant that the pharmacist–psychiatrist collaborative patient education is effective in treatment of BPAD patients. Similar findings were reported by Galuppi et al (2010) wherein positive outcomes in QOL of patients was observed in the study.…”
Section: Discussionsupporting
confidence: 92%
“…This clearly showed improvement in the medication adherence and QOL of the BPAD patients in test group which meant that the pharmacist–psychiatrist collaborative patient education is effective in treatment of BPAD patients. Similar findings were reported by Galuppi et al (2010) wherein positive outcomes in QOL of patients was observed in the study.…”
Section: Discussionsupporting
confidence: 92%
“…The quality of life of patients with schizophrenia can be influenced by unsatisfied needs, including the failure to meet physical health needs, treatment of psychotic symptoms, or financial need . Some studies have found that medication side effects are one factor which could influence the quality of life for people with schizophrenia . In addition, previous studies suggest that nonadherence to antipsychotic medications may result in poor quality of life in patients with schizophrenia (Lasebikan & Owoaje, 2015) …”
Section: Introductionmentioning
confidence: 99%
“…QOL provides the patient's perspective as opposed to conventional health indicators such as mortality and morbidity (Galuppi, Turola, Nanni, Mazzoni, & Grassi, 2010). QOL is a person's sense of well-being, health status and satisfaction with life circumstances, including access to resources and opportunities.…”
Section: Introductionmentioning
confidence: 99%